Corrigendum to "Projective synchronization for fractional neural networks". (July 2015) - Yu, Juan; Hu, Cheng; Jiang, Haijun
Abstract: In this letter, we indicate that the conditions in Lemma 2 in Yu et al. (2014) are not sufficient. To correct the mistake, a new version is given, which provides a sufficient and necessary condition in the sense of Caputo's fractional derivation to verify the monotonicity of the addressed function. Furthermore, a new fractional-order differential inequality is derived, which shows that the main results in Yu et al. (2014) are still true although Lemma 2 has to be modified.